Development of an Android-Based Daily Prayer Learning Application - Saluky; Santinah; Marinih (PT Ilmu Inovasi Nusantara, 2024)
The growing accessibility of information technology offers significant potential for developing educational applications, including those for religious learning. One pressing need is for effective tools to learn daily prayers, essential in Muslim life. This article details the creation of an Android-based daily prayer learning application designed to aid users in learning and memorizing these prayers. The application was developed in four stages: user needs analysis through surveys and interviews, intuitive user interface design, application development using Android Studio with Java, and rigorous testing via Black-box Testing and user trials. Key features include complete prayer texts with translations, audio recitations, and explanations of prayer contexts and benefits. Testing results were positive, with users praising the app’s effectiveness, user-friendly interface, and high-quality content. By leveraging Android’s popularity and affordability, this application provides an accessible and interactive learning platform, addressing the urgent need for a practical medium to enhance daily prayer knowledge and skills among Muslims.